The Relationship of Anxiety with Learning Concentration Levels in the Era of COVID-19 Pandemic on Students of Faculty of Medicine YARSI University Class 2020 and its Review from Islam Perspective - Nadisa Ardikha Prameswari; Kenconoviyati Kenconoviyati; Muhammad Arsyad (Junior Medical Journal, 2022)
Background: The transmission of the COVID-19 outbreak caused by the SARS-CoV-2 virus has spread widely and worldwide, resulting in a pandemic status. Countries are making various efforts to break the chain of the spread of the COVID-19 outbreak, one of which is by adopting a lockdown and self-quarantine policy. Various policies during the pandemic had an impact on the psychological condition of the community, including anxiety that could affect the level of learning concentration. The purpose of this study was to determine the relationship between anxiety and the level of learning concentration in the era of COVID-19 pandemic on class 2020 students of the YARSI University Faculty of Medicine and its review from an Islamic perspective.Method: This study uses an analytical observational method with a cross-sectional approach. The method that was used to determine the sample in this study is random sampling method with a total sample of 149 respondents. Data collected by distributing questionnaires via google form and data analysis using Spearman Rank correlation test.Results: The results showed that the level of anxiety was mostly experienced in mild anxiety, which is 101 respondents and the learning concentration level was mostly in the moderate category, which is 97 respondents. Based on the statistical test, the p-value or p = 0.001 and the correlation value = -0.261.Conclusion: There is a low correlation between anxiety and the level of learning concentration in the era of COVID-19 pandemic among class 2020 students of YARSI University Faculty of Medicine.